Nanosized, peptide-based multicomponent DNA delivery systems: optimization of endosome escape activity. (April 2016) - Wan, Yu; Moyle, Peter M; Christie, Michelle P; Toth, Istvan
Aim: Endosome escape is essential for developing effective nonviral gene delivery systems. Herein, three endosome-disrupting peptides (HA2(1–20), GALA and KALA) were incorporated into a multicomponent oligonucleotide delivery system to identify which peptide imparted the most favorable endosome escape and toxicity profile.Materials & methods: Copper (I)-catalyzed azide-alkyne cycloaddition was used to construct multicomponent delivery vectors. The systems were evaluated for size, toxicity, cellular uptake and endosome escape activity.Results: Each system condensed plasmid DNA to form nanosized particles. The highest cellular uptake and endosome escape were associated with GALA and KALA containing systems, with KALA incorporation correlating with greater toxicity.Conclusion: GALA was selected as the most promising endosome-disrupting peptide for incorporation into the nanosized oligonucleotide delivery system.